Ways to improve the mechanism of investment attraction to economy of Kazakhstan - Айтуганова, З.; Абжанов, С. (Journal of Economic Research & Business Administration, 2017)
The President’s address to the people of Kazakhstan in 2016 “is merely a new global climate diversified economy can withstand the effects of the global crisis. That is why we are working on the implementation of the industrialization program. We need a new investment policy should be, “he noted, effective use of foreign investment in the country’s economy and engaging in mutually beneficial economic cooperation between the two countries is the basis of directions. In fact, with the help of foreign investments deformed to improve the industrial structure of the economy, the creation of new high-tech production, fixed assets and equipment upgrades. Relevance of the work due to the fact that foreign investment as an objectively necessary process for Kazakhstan contributes to curb the crisis and the financial stabilization of the economy, solve the strategic and tactical objectives of macroeconomic nature, such as the fight against inflation, structural adjustment, the elimination of technological and managerial backwardness of the economy. The objective of attracting foreign investments to the country’s economy is a necessary process.